Inhibition of iNOS as a novel effective targeted therapy against triple-negative breast cancer. Issue 1 (December 2015) - Granados-Principal, Sergio; Liu, Yi; Guevara, Maria; Blanco, Elvin; Choi, Dong; Qian, Wei; Patel, Tejal; Rodriguez, Angel; Cusimano, Joseph; Weiss, Heidi; Zhao, Hong; Landis, Melissa; et al.
Abstract Introduction Triple-negative breast cancer (TNBC) is an aggressive form of breast cancer with no effective targeted therapy. Inducible nitric oxide synthase (iNOS) is associated with poor survival in patients with breast cancer by increasing tumor aggressiveness. This work aimed to investigate the potential of iNOS inhibitors as a targeted therapy for TNBC. We hypothesized that inhibition of endogenous iNOS would decrease TNBC aggressiveness by reducing tumor initiation and metastasis through modulation of epithelial-mesenchymal transition (EMT)-inducing factors. Methods iNOS protein levels were determined in 83 human TNBC tissues and correlated with clinical outcome. Proliferation, mammosphere-forming efficiency, migration, and EMT transcription factors were assessedin vitro after iNOS inhibition. Endogenous iNOS targeting was evaluated as a potential therapy in TNBC mouse models. Results High endogenous iNOS expression was associated with worse prognosis in patients with TNBC by gene expression as well as immunohistochemical analysis. Selective iNOS (1400 W) and pan-NOS (L-NMMA and L-NAME) inhibitors diminished cell proliferation, cancer stem cell self-renewal, and cell migrationin vitro, together with inhibition of EMT transcription factors (Snail, Slug, Twist1, and Zeb1). Impairment of hypoxia-inducible factor 1α, endoplasmic reticulum stress (IRE1α/XBP1), and the crosstalk between activating transcription factor 3/activating transcription factor 4 and transforming growth factor β was observed. iNOS inhibition significantly reduced tumor growth, the number of lung metastases, tumor initiation, and self-renewal. Conclusions Considering the effectiveness of L-NMMA in decreasing tumor growth and enhancing survival rate in TNBC, we propose a targeted therapeutic clinical trial by re-purposing the pan-NOS inhibitor L-NMMA, which has been extensively investigated for cardiogenic shock as an anti-cancer therapeutic.